Surpassing the love of men: Romantic friendship and love between women from the renaissance to the present. - Faderman, Lillian (W Morrow, 1981)
A classic of its kind, this fascinating cultural history draws on everything from private correspondence to pornography to explore five hundred years of friendship and love between women.Surpassing the Love of Men throws a new light on shifting theories of female sexuality and the changing status of women over the centuries.
https://feministebooks.files.wordpress.com/2017/01/surpassing-the-love-of-men-romantic-friendship-and-love-between_nodrm.pdf
Keywords: amitié; amour; approches et analyses; corps; droits des femmes*; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; phallocratie; ressource en ligne; sexualité; systèmes d'oppressions; thématiques

Visions partielles, visions partiales: visions des minoritaiers en sociologies - JUTEAU-LEE, Danielle (Sociologie et sociétés, 1981)
Résumé L'irruption du discours des minoritaires en sociologie fait éclater le discours des majoritaires en provoquant la remise en question de leurs explications à tendance naturaliste, culturaliste et psychologisante. Affichant le caractère partiel et partial de leurs visions, les femmes et les "ethniques" favorisent l'éclosion de synthèses provisoires, susceptibles de rendre compte des formes multiples de l'oppression
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; patriarcat; point de vue situé; pol4212; premier cycle; racisme; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; universalisme